The medicinal benefits, phytochemical constituents and antioxidant properties of banana blossom: a mini review / Nur Syahirah Muhammad Suffi ... [et al.] - Muhammad Suffi, Nur Syahirah; Mohamed, Emida; Camalxaman, Siti Nazrina; Rambely, Azlin Sham; Haron, Norhisham (Faculty of Health Sciences, Universiti Teknologi MARA, 2021)
Banana (Musaceae spp.) is a well-known food crop, mainly consumed as a significant yield in most developing countries. However, its blossoms will always end up as agriculture wastes. These by-products are also rich in bioactive compounds and are highly required for our health maintenance. Recent studies have reported that banana blossom contains comparable phytochemical contents. Therefore, this review aims to study the phytochemical constituents, antioxidant properties and medicinal benefits of banana blossoms, making it a potential functional food with diverse nutraceutical values. Several databases such as Web of Science, Scopus, PubMed, Science Direct and Google Scholar were used in this review. Banana blossom also contain bioactive compounds such as phenolics, flavonoids, dietary fibers, tannins, saponins and vitamins. Moreover, banana blossom has potential biological activities such as antioxidant, antihyperglycemic, anti-inflammatory, and antimicrobial properties. Thus, it can be concluded that banana blossoms contain appropriate quantities of beneficial secondary metabolites that are significant in maintaining good health. More research into the medicinal potential of banana blossom can be done to provide new approaches to treating and preventing a variety of medical conditions.